Correction: Molecular-scale thermoelectricity: as simple as 'ABC'. Issue 2 (11th January 2021) - Ismael, Ali; Al-Jobory, Alaa; Wang, Xintai; Alshehab, Abdullah; Almutlg, Ahmad; Alshammari, Majed; Grace, Iain; Bennett, Troy L. R.; Wilkinson, Luke A.; Robinson, Benjamin J.; Long, Nicholas J.; Lambert, Colin
Abstract : Correction for 'Molecular-scale thermoelectricity: as simple as 'ABC'' by Ali Ismael et al., Nanoscale Adv., 2020, 2, 5329–5334, DOI: ; 10.1039/D0NA00772B .